2011
DOI: 10.1103/physrevb.83.014509
|View full text |Cite
|
Sign up to set email alerts
|

Spin and charge fluctuations inα-structure layered nitride superconductors

Abstract: To explore conditions underlying the superconductivity in electron-doped TiNCl where Tc = 16 K, we calculate the electronic structure, Wannier functions and spin and charge susceptibilities using first-principles density functional theory. TiNCl is the first high-temperature superconductor discovered in the α-structure of the layered transition-metal nitride family MNCl (M=Ti, Zr, Hf). We construct a tight-binding model based on Wannier functions derived from the band structure, and consider explicit electroni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…22 As mentioned in the previous paragraph, the T c dependence to the d spacing of the TiNCl intercalation compounds is quite different from that of β-MNCl (M = Zr, Hf). The β-form compounds have a disconnected cylindrical Fermi surface favorable for nesting, 15,16 while the electron-doped α-structured TiNCl has a single oval Fermi surface centered at the point, 27 suggesting that the possible nesting of Fermi surfaces discussed for the β-form compounds should be excluded in the TiNCl compounds. The anisotropic properties on H c2 are quite different between the αand β-structured compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 As mentioned in the previous paragraph, the T c dependence to the d spacing of the TiNCl intercalation compounds is quite different from that of β-MNCl (M = Zr, Hf). The β-form compounds have a disconnected cylindrical Fermi surface favorable for nesting, 15,16 while the electron-doped α-structured TiNCl has a single oval Fermi surface centered at the point, 27 suggesting that the possible nesting of Fermi surfaces discussed for the β-form compounds should be excluded in the TiNCl compounds. The anisotropic properties on H c2 are quite different between the αand β-structured compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Harshman et al 6 have discussed the importance of the Coulomb interlayer coupling and 2D carrier concentration in layered high-T c superconductors. Yin et al 27 also proposed a possible pairing assisted by charge fluctuations in nonmagnetic TiNCl superconductors. Bill et al 7 proposed the importance of electronic collective modes to explain the relatively high T c of β-HfNCl intercalation compounds and showed that even if the structure has strong anisotropy, it cannot be reduced to a purely 2D model, and interlayer Coulomb interaction should be taken into account for superconductivity.…”
Section: Resultsmentioning
confidence: 99%
“…The small anisotropy on H c2 and the Coulomb coupling between the superconducting layers should be the relevant nature of the superconductivity of the α -form layered nitrides [57]. For more discussion on the superconducting mechanisms and the anisotropy of the two different kinds of layered nitrides, a theoretical study including the electric band structure is required [328]. …”
Section: New Superconductorsmentioning
confidence: 99%
“…It will be interesting to compare their superconductivities. The β-structured compounds have disconnected cylindrical Fermi surfaces favorable for nesting [13,35,77], while the electron-doped α-structured TiNCl has a simple oval shaped Fermi surface around only the Γ point [78], suggesting that a similar possibility of the nesting is excluded. …”
Section: Tincl By Intercalationmentioning
confidence: 99%